# Laplace’s equation

Laplace’s equation in polar coordinates

November 1, 2008

Laplace’s equation in polar coordinates

Laplace’s equation

Laplace’s equation in (x, y ) coordinates

∇2 f = 0 i.e. ∂2f ∂2f + 2 =0 ∂x 2 ∂y

Laplace’s equation in polar coordinates

Laplace’s equation

In polar coordinates...

∇2 f =

1 ∂ r ∂r

r

∂f ∂r

=

∂2f ∂f ∂2f 1 ∂2f = r2 2 + r + 2 r 2 ∂θ 2 ∂r ∂r ∂θ

i.e. ∇2 f = 0 becomes r2 ∂f ∂2f ∂2f +r + 2 =0 ∂r 2 ∂r ∂θ

Laplace’s equation in polar coordinates

Laplace’s equation Why do it? We use particular co-ordinate systems to solve problems with particular geometries. The correct co-ordinates to use are polar co-ordinates. Laplace’s equation in polar coordinates . Consider a circular plate with some temperature distribution on its boundary.

If the solution doesn’t satisfy this condition get rid of it immediately. Check that the solution at θ = 2π is the same as the solution at θ = 0. Laplace’s equation in polar coordinates .Laplace’s equation Two new ideas Check that the solution doesn’t become inﬁnite at some point in space. If it does get rid of the solution.

Laplace’s equation Separation of variables We look for solutions of the form f (r . θ) = R(r )T (θ) Substituting into r2 gives r 2 R (r )T (θ) + rR (r )T (θ) + R(r )T (θ) = 0 ′′ ′ ′′ ∂2f ∂f ∂2f +r + 2 =0 2 ∂r ∂r ∂θ Laplace’s equation in polar coordinates .

so both must be equal to a constant: r 2 R (r ) + rR (r ) T (θ) =− = const. R(r ) T (θ) ′′ ′ ′′ ′′ ′ ′′ ′′ ′ ′′ Laplace’s equation in polar coordinates .Laplace’s equation Separation of variables Rearranging r 2 R (r )T (θ) + rR (r )T (θ) + R(r )T (θ) = 0 gives T (θ) r 2 R (r ) + rR (r ) =− R(r ) T (θ) Each side is a function of a diﬀerent variable.

Laplace’s equation Case 1: positive constant We call the constant λ2 and assume λ = 0 r 2 R (r ) + rR (r ) = λ2 R(r ) i.e. So we look for solutions of the form r m . ′′ ′ ′′ ′ Laplace’s equation in polar coordinates . r 2 R (r ) + rR (r ) − λ2 R(r ) = 0 This is an ODE with coeﬃcients which are powers matching the derivative.

m = ±λ So the general solution is R(r ) = c1 r λ + c2 r −λ Laplace’s equation in polar coordinates . m(m − 1) + m − λ2 = 0 i. m2 − λ2 = 0 i.e.e.e.Laplace’s equation Case 1: positive constant Substituting R(r ) = r m into gives r 2 R (r ) + rR (r ) − λ2 R(r ) = 0 ′′ ′ m(m − 1)r m + mr m − λ2 r m = 0 i.

leaving R(r ) = c1 r λ Laplace’s equation in polar coordinates .Laplace’s equation Using some physical knowledge Consider the general solution R(r ) = c1 r λ + c2 r −λ What happens to r −λ at r = 0? To avoid solutions which become inﬁnite we discard the term c2 r −λ .

i.e. so the value of T (θ) must be the same at 0 and at 2π.e. Again we need some physical knowledge.Laplace’s equation Case 1: positive constant The θ equation is: T (θ) = −λ2 T (θ) ′′ i.e.e. cos(λ0) = cos(2πλ) 1 = cos(2πλ) and and sin(λ0) = sin(2πλ) 0 = sin(2πλ) The ﬁrst is only satisﬁed if λ is an integer n. I. θ is an angle. In this case the second equation is also satisﬁed. λ=n Laplace’s equation in polar coordinates . T (θ) + λ2 T (θ) = 0 ′′ We know that this is solved by linear combinations of sin(λθ) and cos(λθ). i.

Laplace’s equation Case 1: positive constant So ﬁnally in the case of a positive constant we get the solution f (r . θ) = r n (A cos nθ + B sin nθ) Laplace’s equation in polar coordinates . θ) = c1 r n (d1 cos nθ + d2 sin nθ) Renaming some constants gives f (r .

e. since θ is an angle we require T (0) = T (2π). T (θ) − µ2 θ = 0 The general solution of this equation consists of linear combinations of e µθ and e −µθ . i.Laplace’s equation Case 2: negative constant We call the constant −µ2 and assume µ = 0. ′′ ′′ Laplace’s equation in polar coordinates . So there are no physically meaningful solutions with a negative constant. Looking ﬁrst at the θ equation: T (θ) = µ2 θ i. As before. and e −µ0 = 1 = e −2πµ e µ0 = 1 = e 2πµ This only has solution µ = 0 whereas we have assumed that µ = 0.e.

Laplace’s equation Case 3: zero constant The θ equation becomes T (θ) = 0 i. c3 = 0 ′′ Laplace’s equation in polar coordinates .e. T (θ) = c3 θ + c4 Insisting that T (2π) = T (0) gives c3 2π + c4 = c3 0 + c4 i.e.

e. m2 = 0 i. so the two solutions are r0 giving R(r ) = d3 r 0 + d4 ln r and ln r Laplace’s equation in polar coordinates . m = 0 ′′ ′ This is a repeated root.e.Laplace’s equation Case 3: zero constant The r equation becomes r 2 R (r ) + rR (r ) = 0 We try r m giving m(m − 1) + m = 0 i.

both R(r ) and T (θ) are just constants so we can write R(r )T (θ) = C Laplace’s equation in polar coordinates .Laplace’s equation Case 3: zero constant What happens to ln r as r → 0? As before we get rid of unphysical behaviour and get R(r ) = d3 r 0 = d3 So in the case of a zero constant.

θ) = C + n r n (An cos nθ + Bn sin nθ) Laplace’s equation in polar coordinates .Laplace’s equation The “general solution” We thus get the general solution: f (r .

Laplace’s equation A circular plate with radius r0 Consider a circular plate with radius r0 and some temperature T = g (θ) along the boundary (i. at r = r0 ).e. θ) = g (θ) Laplace’s equation in polar coordinates . outer perimeter: θ r0 f (r0 .

θ) = C + n r0 n (An cos nθ + Bn sin nθ) Remember that the Fourier series for g (θ) is g (θ) = 1 a0 + 2 (an cos nθ + bn sin nθ) n Laplace’s equation in polar coordinates .Laplace’s equation Substituting in the boundary conditions f (r . θ) = C + n r n (An cos nθ + Bn sin nθ) Substituting in the boundary condition: g (θ) = f (r0 .

Laplace’s equation in polar coordinates .Laplace’s equation Substituting in the boundary conditions Comparing g (θ) = f (r0 . r0 Bn = bn n r0 where an and bn are the Fourier coeﬃcients for g (θ). θ) = C + n r0 n (An cos nθ + Bn sin nθ) and g (θ) = gives 1 a0 + 2 (an cos nθ + bn sin nθ) n 1 C = a0 . 2 An = an n.

Laplace’s equation Substituting in the boundary conditions So the full solution is: 1 f (r . θ) = a0 + 2 r r0 n (an cos nθ + bn sin nθ) n where an and bn are the Fourier coeﬃcients for g (θ). Laplace’s equation in polar coordinates .

so a0 = 2. θ) = a0 + 2 reduces to: f (r . θ) = 1 + r r0 n (an cos nθ + bn sin nθ) n r r0 sin θ Laplace’s equation in polar coordinates . bn = 0 (n ≥ 2) The general solution 1 f (r .Laplace’s equation Example 1 The temperature varies periodically around the perimeter g (θ) = 1 + sin θ Here the Fourier series is in the function itself. an = 0 (n ≥ 1). b1 = 1.

0 1 y 0. 0. -1 -1 -0. 1.Laplace’s equation What the solution looks like 1 2 1. 0.5 1 0 Laplace’s equation in polar coordinates . 0. -0. 1.5 0 x 0.5 1.5 0.

5 1 0. an = 0 (n ≥ 1) bn = 0 (n = 5) T 2 1.5 1-1 y Laplace’s equation in polar coordinates . b5 = 1.5 x 0 0 0. so a0 = 2.5 -0.5 -1 -0.5 0 0. oscillating faster g (θ) = 1 + sin 5θ Here the Fourier series is in the function itself.Laplace’s equation Example 2 The temperature varies periodically around the perimeter.

θ) = a0 + 2 reduces to: f (r .Laplace’s equation Example 2 The general solution 1 f (r . θ) = 1 + r r0 r r0 n (an cos nθ + bn sin nθ) n 5 sin 5θ Laplace’s equation in polar coordinates .

5 1-1 y Laplace’s equation in polar coordinates .Laplace’s equation What the solution looks like 2 1.5 x 0 0 0.5 0 1 0.5 -0.5 -1 -0.5 T 1 0.

1.5 1 0 Laplace’s equation in polar coordinates .5 1. 0. 0. -0.5 0.5 0 x 0. 0 1 y 0.Laplace’s equation What the solution looks like 1 2 1. -1 -1 -0. 0. 1.

Laplace’s equation Example 3 Consider g (θ) = 0 −π ≤ θ < 0 1 0≤θ<π So that the top half of the plate is held at a temperature of 1 while the bottom half is held at a temperature of 0 Laplace’s equation in polar coordinates .

Laplace’s equation Example 1 Calculating the Fourier series of g (θ) = gives a0 = 1. bn = 0 n even (2/nπ) n odd 0 −π ≤ θ < 0 1 0≤θ<π So the full solution is f (r . θ) = 1 2 + 2 π n odd r r0 n sin nθ n Laplace’s equation in polar coordinates . an = 0 (for n ≥ 2).

0 y 0.5 0.5 1 -0.Laplace’s equation What the solution looks like Approximation: 1 term 1 1. Laplace’s equation in polar coordinates . -0. 0 -1 -1 -0. 1 0.5 0 x 0.5 0. 0.

Laplace’s equation in polar coordinates . 0 y 0.5 0 x 0.5 0. -0. 0 -1 -1 -0. 0.5 0.5 1 -0.Laplace’s equation What the solution looks like Approximation: 2 terms 1 1. 1 0.

5 0 x 0. 0 -1 -1 -0.5 0. 1 0. -0. 0 y 0.5 0. 0.5 1 -0. Laplace’s equation in polar coordinates .Laplace’s equation What the solution looks like Approximation: 5 terms 1 1.

5 1 -0. 1 0. Laplace’s equation in polar coordinates . -0.Laplace’s equation What the solution looks like Approximation: 20 terms 1 1. 0. 0 -1 -1 -0. 0 y 0.5 0.5 0 x 0.5 0.

0.5 0. 0 -1 -1 -0. Laplace’s equation in polar coordinates . 0 y 0. -0.5 1 -0.5 0.5 0 x 0. 1 0.Laplace’s equation What the solution looks like Approximation: 60 terms 1 1.